Nutrient sequestration from wastewater by using zeolite Na-P1 synthesized from coal fly ash. Issue 8 (18th April 2017) - He, Hongfu; Xu, Suyun; Han, Runqi; Wang, Qiuchen
ABSTRACT: The objective of this study is to investigate the cation exchange property of the product zeolite Na-P1 (Z-P1) synthesized from coal fly ash (FA) by the alkali hydrothermal reaction, and to evaluate the water purification ability for the simultaneous removal of ammonium and phosphate. High-purity Z-P1 was obtained by optimizing the reaction conditions of aging time and crystallization temperature, and using FA particles of uniform particle size. Kinetic ammonium sorption experiments with Z-P1 were well described by both the Langmuir and Freundlich models, and the maximum adsorption capacity of the Z-P1 was 23.15 mg/g. Moreover, in order to determine the effect of magnesium intervention on the ammonium and phosphate removal from simulated swine wastewater, two forms of magnesium were studied, that is Mg-saturated Z-P1 and direct use of Mg 2+ source with Z-P1, as compared with the control (sole Z-P1). Results showed that Mg 2+ addition could improve phosphate removal efficiency significantly by forming struvite. Furthermore, dosing Z-P1 with dissolved Mg 2+ was better than Mg-saturated Z-P1 in terms of ammonium and phosphate removal efficiencies, and the preparation cost. When dosing 20 g/L Z-P1 with 4 mM Mg 2+, ammonium and phosphate removal efficiencies reached 65.2% and 92.3% after 30 min. GRAPHICAL ABSTRACT: